Data integrity verification based on model cloud federation of TPA - Junfeng TIAN; Tianle LI (Tongxin xuebao)
Aiming at the untrustworthiness of third-party auditor (TPA) in the publicity verification model,a data integrity verification model based on the cloud federation of TPA was proposed.Firstly,the cloud federation of TPA’s architecture was designed and the main functional components and function of the system platform was defined.The federation could manage and control the TPA cloud members.Secondly,TPA was designed in detail by using trusted computing technology and blockchain technology to ensure the credibility of the TPA execution environment and workflow.Finally,the data integrity verification model was built by using cloud federation of TPA.The correctness,security and effectiveness of the model were analyzed theoretically and experimentally.